Bridging The Trust Gap: Strategies To Enhance Customer Confidence In International E-Commerce - Shannon Kimberly Lie; Gracia Ongkowijoyo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study investigates the trust gap between international e-commerce platforms and local customers. retailing. A questionnaire was developed and distributed online using a non-probability judgment sample of international e-commerce platform users with the age above 18 in Surabaya, East Java. Data were analyzed using partial least squares (PLS) regression method on SmartPLS software. These research findings reveal perceived security and privacy concerns influence customer trust and loyalty in the context of international e-commerce platforms. Moreover, customer trust acts as a mediating factor between perceived security, privacy concern, and customer loyalty, highlighting its crucial role in fostering positive customer relationships. These results contribute to a deeper understanding of consumer behavior within the Indonesian e-commerce landscape. By identifying and addressing the specific concerns surrounding privacy and security, international e-commerce platforms can attract more Indonesian customers who might otherwise be hesitant to engage with them.